The Role of Electricity and Energy Consumption Influences Industrial Development between Regions in Indonesia - Hadi, Muhammad Fikry; Hidayat, Muhammad; Widiarsih, Dwi; Murialti, Neng (International Journal of Energy Economics and Policy, 2021)
Our research aims to determine the effect of electricity distribution and energy consumption on industrial development dynamics that occur between regions in Indonesia by adding investment and inflation as control variables. The analysis tools that we use are static (Fixed Effect) and dynamic (GMM) panel data model with a dataset of 34 provinces for the 2012-2019 period. The static model results state that the distribution of electricity and investment has a significant positive effect on the industry, and so does energy consumption, but not significantly. In contrast, inflation has a significant negative effect. There are differences in dynamic results, namely, electricity distribution and energy consumption have a negative and significant effect on industrial development. These results suggest different actions in industrial development concerning timeframes. Keywords: Electricity distribution, Energy consumption, Industry, GMM, Indonesia JEL Classifications: C33, O14, Q40 DOI: https://doi.org/10.32479/ijeep.11082